STUDI KRITIS NIKAH TANPA WALI KAJIAN TAFSIR AHKAM QS. AL-BAQARAH: 232 - Ida Mufidah; Masruhan Masruhan (FiTUA: Jurnal Studi Islam, 2021)
One of the crucial issues in marriage is marriage without a guardian which is a problem of khilafiyyah ijtihadiyyah among the ulama' madhhab. One of the verses that is used as a foothold by each party is QS. Al-Baqarah: 232 with different interpretations. This paper attempts to conduct a critical study of the interpretation of the verse regarding the legality of marriage without a guardian. The results of the study conducted show that the difference in the scholars' interpretation of the verse is in the khit}a>b contained in the verse. According to the majority of scholars, the verse is intended for female guardians so that the verse indicates that marriage without a guardian is not valid. Meanwhile, according to the Hanafi school of thought, the verse is aimed at a husband who prevents his ex-wife from marrying someone else so that the verse shows a woman can marry herself without a guardian. Although this is a khilafiyyah problem, marriage without a guardian has the potential to cause a marriage based on consensual only which needs to be avoided.